Dark Mirrors and Dead Ringers: Music for Suspense Films about Twins - Bowman, Durrell (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2006)
This paper compares the modernist musical-narrative separations of The Dark Mirror (Robert Siodmak, 1946), Dead Ringer (Paul Henreid, 1964), and Sisters (Brian De Palma, 1973) with the postmodernist musical-narrative fusions of the Canadian film Dead Ringers (David Cronenberg, 1988). The two earlier films (starring Olivia de Havilland and Bette Davis, respectively) mainly conform to the aesthetic of film noir or "suspense-thriller," whereas the two later films (starring Margot Kidder and Jeremy Irons, respectively) also contain substantial elements of "horror." The musical scores of these four films (by Dimitri Tiomkin, André Previn, Bernard Herrmann, and Howard Shore) feature, in varying degrees, the meaningful placement and development of leitmotifs and titles music, changes in meaning by altering instrumentation and/or mode, gender representations, and issues of cultural hierarchy and class distinctions.